2021
DOI: 10.1111/tpj.15119
|View full text |Cite
|
Sign up to set email alerts
|

Wheat 2‐Cys peroxiredoxin plays a dual role in chlorophyll biosynthesis and adaptation to high temperature

Abstract: The molecular mechanism of high-temperature stress (HTS) response, in plants, has so far been investigated using transcriptomics, while the dynamics of HTS-responsive proteome remain unexplored. We examined the adaptive responses of the resilient wheat cultivar 'Unnat Halna' and dissected the HTS-responsive proteome landscape. This led to the identification of 55 HTS-responsive proteins (HRPs), which are predominantly involved in metabolism and defense pathways. Interestingly, HRPs included a 2-cysteine peroxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…Furthermore, high- and low-temperature stress in higher plants generates ROS ( 44 , 45 ). In wheat, for example, high-temperature stress conditions induce the expression of 2-Cys Prx, a ROS scavenger ( 46 ). Therefore, ROBINc might be useful for monitoring the redox status in various photosynthetic organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, high- and low-temperature stress in higher plants generates ROS ( 44 , 45 ). In wheat, for example, high-temperature stress conditions induce the expression of 2-Cys Prx, a ROS scavenger ( 46 ). Therefore, ROBINc might be useful for monitoring the redox status in various photosynthetic organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from these well‐characterized genes, many other genes coding for kinases, transcription factors, HSFs and HSPs, are known to regulate either heat stress or root development. However, their molecular mechanisms underlying root development during heat stress needs in planta functional characterization (Dhakate et al, 2021; Mishra et al, 2020; Mishra, Shekhar, et al, 2021; Mittler et al, 2012; Ohama et al, 2017; Tiwari, Pandey, Singh, Yadav, et al, 2021). Investigations involving in planta overexpression of these genes indicated that a better root architecture provides superior support to the overall plant stature.…”
Section: Physio‐morphological and Molecular Dynamics Associated With ...mentioning
confidence: 99%
“… Huang et al (2020) reported that arbuscular mycorrhizal fungi (AMF) could utilize the MAPKs signaling pathway to enhance drought tolerance by using MAPK signaling as an intermediate pathway for interactions between AMF and their host apple plant. Besides, the extensive role of MAPKs, other kinases such as histidine kinases, CDPKs, leucine-rich repeat-receptor-like kinases, and serine-threonine protein kinases are also at the center of stress tolerance ( Mishra et al, 2021a ; Tiwari et al, 2021a , b ). Early leaf development is regulated by genes-encoding OsSIK2 , a protein kinase located in rice leaf and sheath plasma membrane.…”
Section: Influence Of Reactive Oxygen Species-antioxidative System On Plant Processesmentioning
confidence: 99%
“…ROS production is directly related to stress in plants and leads to membrane damage and subsequent stress signaling ( Mishra et al, 2017 , 2018 ). ROS production takes place in the reaction centers of photosystem I (PSI) and PSII in chloroplast thylakoids ( Foyer, 2018 ; Mishra et al, 2021a ). ROS species formation is a result of the direct transfer of the excitation energy from chlorophyll to produce singlet oxygen, or by oxygen reduction in the Mehler reaction ( Foyer, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation